Closed loop pulsating heat pipes - Part B: Visualization and semi-empirical modeling - Khandekar S. (2014)
Pulsating heat pipes have received growing attention from experimental and theoretical researchers in recent times. Behind its constructional simplicity lie the intriguingly complex thermo-hydrodynamic operational characteristics. Part A of this paper has presented the thermal performance results of a fairly large matrix of closed loop pulsating heat pipes. This paper, which is an extension of the previous work, first presents some more visualization results to highlight the complexities involved in mathematical formulation of the modeling problem. The phenomenological trends recorded in the visualization set-up are fully inline with the previous quantitative data of Part A. Critical review of the existing modeling approaches to CLPHPs is presented in the wake of these results. A detailed discussion follows on the important issues involved in the mathematical modeling of these devices. Then, semi-empirical correlations based on non-dimensional numbers of interest for predicting the thermal performance of CLPHPs are presented. Although there are limitations of the models presented herein, modeling by non-dimensional numbers seems to be most promising as compared to other existing techniques. © 2003 Elsevier Ltd. All rights reserved.